BacA(SbmA) importer of legume symbiotic NCR peptides: Protein architecture, function, and evolutionary implications - Markus F. F. Arnold; Siva Sankari; Michael Deutsch; Charley C. Gruber; Francisco J. Guerra-Garcia; Konstantinos Beis; Graham C. Walker (Proceedings of the National Academy of Sciences, 2026)
Some legumes encode families of NCR (Nodule-Cysteine-Rich) peptides that cause their rhizobial partners to terminally differentiate during the development of a nitrogen-fixing symbiosis. Sinorhizobium meliloti, whose plant hosts Medicago truncatula and Medicago sativa express ca. 600 NCR peptides during root nodule development, possesses a symbiotically essential BacA Sm protein that imports certain NCR peptides into the cytoplasm. This import permits proteolytic degradation of the NCR peptides, thereby protecting the endocytosed bacteria from their antimicrobial peptide-like lethality, while also allowing certain NCR peptides to undergo their symbiotically critical interactions with cytoplasmic components, for example heme-sequestration in the case of NCR247. Our study employed 54 S. meliloti bacA Sm missense mutants (35 to cysteine and 19 to glycine) that we tested for protein production, ability to establish a nitrogen-fixing symbiosis, and their susceptibility to killing by higher levels of the NCR247 and the Bac7(1-35) peptides. We also used the Single Cysteine Accessibility Method to make topological inferences. Our detailed genetic, biochemical, structural, and physiological analyses have revealed that BacA Sm and SbmAhomodimers function as finely tuned transporters, whose structures can be relatively easily disrupted by single amino acid changes. Our finding that several mutations that differentially separate nitrogen-fixation, NCR247 import, and Bac7(1-35) import map to the lining of the peptide-binding cavity suggests a molecular explanation underlying the paradoxical observation that SbmA/BacAs from pathogens can fully replace BacA Sm , whereas BacAs from other rhizobia cannot.